Stabilisasi Tanah Ekspansif Menggunakan Serbuk Cangkang Telur Dengan Tambahan Kapur Sebagai Zat Aditif - Mohammad Arhoillah Hasan (Jurnal Vokasi Teknik Sipil, 2024)
Soil is the basis of a building structure. Each region has varied soil characteristics and properties. Expansive land is often a problem for some construction service providers because it has bad properties. Expansive soil stabilization action is a method that can reduce the poor properties of expansive soils. Eggshell powder is organic waste that is almost every day and has not been used properly. The use of eggshells as a mixture of soil improvement can be one of the uses of eggshell waste. Lime is one of the chemicals that become an ingredient for soil stabilization. Lime contains pozzolan substance, which is the same substance as Portland Cement which at certain levels and treatments reacts to changes in the mechanical properties of expansive soil. This study used an experimental method by providing a variety of test specimens located on the content of a mixture of eggshell powder on expansive soil, namely 0%, 10%, 20%, and 30% with a mixture of 10% lime as an additive, namely lime. The percentage of effective addition of eggshell powder to a mixture of 10% lime + 20% eggshell powder can increase the plastic limit value and decrease the liquid limit.